Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1021/acschemneuro.8b00265
|View full text |Cite
|
Sign up to set email alerts
|

Stress-Induced Alterations of Norepinephrine Release in the Bed Nucleus of the Stria Terminalis of Mice

Abstract: Stress can drive adaptive changes to maintain survival during threatening stimuli. Chronic stress exposure, however, may result in pathological adaptations. A key neurotransmitter involved in stress signaling is norepinephrine. Previous studies show that stress elevates norepinephrine levels in the bed nucleus of the stria terminalis (BNST), a critical node regulating anxiety and upstream of stress responses. Here, we use mice expressing channelrhodopsin in norepinephrine neurons to selectively activate termin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
31
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 38 publications
6
31
0
Order By: Relevance
“…Here, PCUS significantly elevated only norepinephrine levels vs. controls. Given that stress increases the activity of the sympathetic nervous system, this observation parallels rodent data where stress also increases norepinephrine 52 , 53 . A widely used SSRI, fluoxetine, decreased 5-HIAA (the main metabolite of serotonin) in zebrafish brain, as well as the ratio of 5-HIAA/serotonin (vs. control group), reflecting lower serotonin turnover, a common biomarker of SSRI antidepressant action in zebrafish models 54 , 55 .…”
Section: Discussionsupporting
confidence: 79%
“…Here, PCUS significantly elevated only norepinephrine levels vs. controls. Given that stress increases the activity of the sympathetic nervous system, this observation parallels rodent data where stress also increases norepinephrine 52 , 53 . A widely used SSRI, fluoxetine, decreased 5-HIAA (the main metabolite of serotonin) in zebrafish brain, as well as the ratio of 5-HIAA/serotonin (vs. control group), reflecting lower serotonin turnover, a common biomarker of SSRI antidepressant action in zebrafish models 54 , 55 .…”
Section: Discussionsupporting
confidence: 79%
“…This finding was supported by Fan et al, 2014 who reported that Cort treatment for 21 days induced a significant increase in dopamine-β-hydroxylase protein (DβH) and nor-epinephrine transporter protein expression (NET) in the brain, and that this effect was counteracted by concomitant treatment with a corticosteroid receptor antagonist (mifepristone), in addition to spironolactone 67 . The changes of NET and DβH expression that was induced by Cort is a normal response to stress and was accompanied by increased stressful behaviours 68 . The effect of Cort on norepinephrine was minimized by treatment with oleuropein or fluoxetine and maintained nor-epinephrine level compared to that of the control group.…”
Section: Discussionmentioning
confidence: 99%
“…Acute restraint also causes an increase in corticosterone release in mice, but this change is significantly attenuated in PACAP- and PAC1-deficient mice, suggesting that PACAP-PAC1 receptor binding in BNST may mediate central short-term effects of restraint stress (Mustafa et al, 2015). Relatedly, acute stress (i.e., a short, potent stressor) has been shown to elevate norepinephrine in the BNST: Schmidt et al (2018) showed, using optogenetic-assisted fast-scan cyclic voltammetry, elevated norepinephrine release across several stimulation parameters and reduced sensitivity to norepinephrine auto-receptors in mice exposed to 5 days restraint stress. In contrast to reports of acute restraint, chronic immobilization increases BNST (but not amygdala) dendritic branching (Vyas et al, 2003), suggesting a role of stress in remodeling neurons in stress-related brain regions after the traumatic event that underlies PTSD.…”
Section: Animal Models Of Ptsdmentioning
confidence: 99%